FEMINIST LITERARY CRITIQUE OF WOMEN’S REPRESENTATION IN NAGUIB MAHFOUZ’S LAYALI ALF LAYLAH - Alandira, Palendika; Ainusyamsi, Fadlil Yani; Rohanda, Rohanda (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This research examines the portrayal of women in Arabian Nights and Days by Naguib Mahfouz through the lens of feminist literary criticism, focusing on the character of Dunyazad. The analysis explores her physical, psychological, and social dimensions, emphasizing how these aspects reflect broader societal perceptions and treatment of women. Employing a qualitative approach, the research utilizes feminist theory to uncover the depiction of Dunyazad and her interactions within the social context of the novel, which mirrors the condition of women in the Arab world. The formal object of this study is feminist literary criticism theory, while the material object is Mahfouz’s novel. The study is confined to analyzing Dunyazad’s character and her relationship with societal norms. Findings reveal that the representation of women in the novel is shaped by three main elements: physical idealization, psychological conflict, and social subordination, all of which are framed by patriarchal structures. Dunyazad’s physical portrayal reinforces the objectification of women, her psychological depiction reflects the inner turmoil of women constrained by social expectations, and her social portrayal underscores the systemic subjugation of women. In conclusion, Mahfouz critiques the societal norms that restrict women’s roles and exposes the persistence of gender inequality within patriarchal societies.